To solve \(7 \frac{5}{10} - 1 \frac{6}{10}\), we'll first convert the mixed numbers into improper fractions.
-
Convert \(7 \frac{5}{10}\): \[ 7 \frac{5}{10} = \frac{7 \times 10 + 5}{10} = \frac{70 + 5}{10} = \frac{75}{10} \]
-
Convert \(1 \frac{6}{10}\): \[ 1 \frac{6}{10} = \frac{1 \times 10 + 6}{10} = \frac{10 + 6}{10} = \frac{16}{10} \]
Now, we can perform the subtraction: \[ \frac{75}{10} - \frac{16}{10} = \frac{75 - 16}{10} = \frac{59}{10} \]
Next, convert \(\frac{59}{10}\) back into a mixed number: \[ \frac{59}{10} = 5 \frac{9}{10} \]
Thus, the correct result of \(7 \frac{5}{10} - 1 \frac{6}{10}\) is: \[ \boxed{5 \frac{9}{10}} \]